Candidaţii prezidenţiabili pe Facebook în timpul protestelor din ianuarie 2012 - Antonio Momoc (Sociologie Românească, 2013)
Raed Arafat’s resignation from his position of Secretary of State within the Ministry of Health on January 10th 2012 ignited the political crisis that took place in January-February 2012 and led to a series of street protests, which culminated when the Emil Boc Government resigned on February 9th 2012. The newness of these street movements that happened in Romania’s large cities consisted in the online mobilization of the protesters. The citizens showed online their solidarity with Raed Arafat, the medic who opposed the Government’s intentions to change the Sanitary System Law. According to the Secretary of State, the reform would have liberalized the health services, which would have affected the low income population, as well as the Public Emergency Ambulance Service. The social networks users organized in online communities of supporters, and the members of these groups settled and communicated online the time and meeting place where they gathered to shout anti-governmental and anti-presidential slogans every evening. The Romanian politicians, especially the potential candidates for the 2014 presidential elections, have not remained indifferent. Most of them reacted in an effort to improve their image and their level of trust among the protesters, who have organized themselves through social media. Using the content analysis method applied on the politicians’ official Facebook accounts, this article presents the quick reactions, and the image and communication strategies that the presidential candidates resorted to during the protests started on the social networks in January 2012.